Analisis Kemajuan Berbagai UMKM dalam Pemasaran di Desa Tegalwaru, Kabupaten Bogor, Jawa Barat - Arya Dwi Praja Usman; Syifa Khoirunnisa; Siti Fitriah; Muhamad Bagus Jatmiko; Bonar Tua Sihite; Nike Nurindah RSB; Agief Julio Pratama; M. Iqbal Nurulhaq; Tri Budiarto; Widya Hasian Situmeang; Ratih Kemala Dewi; Restu Puji Mumpuni; Edi Wiraguna (Harmoni Sosial : Jurnal Pengabdian dan Solidaritas Masyarakat, 2025)
Tegalwaru Village in Ciampea District, Bogor Regency, possesses substantial potential for sustainable Micro, Small, and Medium Enterprise (MSME) development, yet faces challenges in marketing and digital adoption. This study aims to analyze the progress of MSMEs in Tegalwaru, focusing on production, marketing strategies, and ecotourism integration to enhance economic growth. Using a qualitative descriptive approach, data was collected through in-depth interviews with MSME actors, field observations, and document analysis. Findings indicate that while MSMEs have advanced in product diversification and production capacity, their growth is hindered by limited digital marketing skills and inadequate access to capital. Conversely, the village’s rich natural and cultural resources present significant opportunities for ecotourism, which could synergize with MSMEs to boost local income sustainably. The study highlights the need for targeted interventions, including digital literacy training, improved financing access, and collaborative efforts among MSMEs, local government, and tourism stakeholders. By strengthening these aspects, Tegalwaru can achieve holistic MSME development, fostering economic resilience and community welfare. The research underscores the importance of integrating MSMEs with ecotourism as a strategy for inclusive and sustainable rural development.